Efecto de sustancias minerales altamente diluidas (smads) en el cultivo hidropónico en plantas de lechuga (Lactuca sativa L - Morán Villacreses, Enma Leonor (2021)
Lettuce is the leafy vegetable most consumed worldwide, however it is still necessary to optimize its cultivation, using new sustainable technologies. The present research had the objective to evaluate the effect of SMADs in the hydroponic growth of lettuce (Lactuca sativa L.) to determine the best treatment. The experiment had four treatments: Silicea terra, Natrum muriaticum, a combination of Silicea and Natrum and a control group (no SMADs). The experiment was established as a completely randomized design with three repetitions. Each experimental unit (commercial hydroponic kit) had six plants, where they reach emergency and vegetative growth phase. The germination phase was done in Petri dishes, where the seeds where previously embedded with each treatment. The evaluated variables were percentage and germination rate, and emergency and morphometric variables. Additionally physical-chemical, microbiological factors and nutrient analysis in plants were determined. The results suggested that Silicea terra improved the germination and seed emergency, while Natrum muriaticum improved the vegetative growth of the different morphometrical variables, showing a bigger root with 39.5 cm, 19 leaves per plant, fresh weight of 19.4 g and dry weight of 0.98 g, compared to the control where 28.16, 11, 13.91 and 0.97 were obtained respectively. Water quality evaluated as UFC where higher in Silicea terra (544) compared to the control (221). The temperature was constant during the experiment (28°C in all treatments), pH was more stable in Natrum, while electrical conductivity showed values in a range of 1500 to 3000 ppm. The SMADs cause favorable effects on the growth and development of lettuce plants grown in a hydroponic system. Keywords: Silicea Terra, Natrum Muriaticum, Agro homeopathy, food safety.